Current State and Prospects of Development of the Sports System of Ukraine: Legal Aspects (Estado actual y perspectivas de desarrollo del sistema deportivo de Ucrania: aspectos legales) - Tkalych, Maxym; Davydova, Iryna; Tolmachevska, Yuliia (Retos, 2020)
The article analyzes the current state of the sports organization system in Ukraine. The authors of the article argue that the sports system in Ukraine needs to be reformed in light of current trends in world sports. First and foremost, the need for regulatory and institutional development of the professional sport, which can have a positive impact on the development of the entire sports system of Ukraine. Currently, the dominant position in Ukrainian sport is occupied by the state and non-governmental organizations. This approach was justified under the conditions of a planned economy during the Soviet Union, but it is now outdated and hinders the development of Ukrainian sport.Instead, modern sport in developed countries is primarily driven by private initiative and the creation of appropriate conditions for a variety of private law entities to promote entrepreneurial activity in sport.The purpose of the article is to identify the key institutional and legal factors of the domestic sports system that negatively affect its development.Adequate regulatory support for commercial sports will give additional funds in domestic sports, which inevitably plays a role in improving sports achievements and restoring Ukraine's position in the world sports arena. The key direction of the development of domestic sports the author sees the further commercialization and professionalization of domestic sports.The authors of the article state that the Ukrainian legislature should as soon as possible turn its attention to the normative provision of sports, in particular - to adopt a number of amendments to the current law "On physical culture and sports" or to adopt a new law on sports and/or the law "On professional sports". El artículo analiza el estado actual del sistema de organización deportiva en Ucrania. Los autores del artículo sostienen que el sistema deportivo en Ucrania necesita ser reformado a la luz de las tendencias actuales en los deportes mundiales. Ante todo, la necesidad de un desarrollo regulatorio e institucional del deporte profesional, que puede tener un impacto positivo en el desarrollo de todo el sistema deportivo de Ucrania. Actualmente, la posición dominante en el deporte ucraniano está ocupada por el estado y las organizaciones no gubernamentales. Este enfoque se justificó bajo las condiciones de una economía planificada durante la Unión Soviética, pero ahora está desactualizado y dificulta el desarrollo del deporte ucraniano.En cambio, el deporte moderno en los países desarrollados está impulsado principalmente por la iniciativa privada y la creación de condiciones apropiadas para una variedad de entidades de derecho privado para promover la actividad empresarial en el deporte.El propósito del artículo es identificar los factores institucionales y legales clave del sistema deportivo nacional que afectan negativamente su desarrollo.El apoyo regulatorio adecuado para los deportes comerciales dará fondos adicionales en los deportes nacionales, que inevitablemente juegan un papel en la mejora de los logros deportivos y en la restauración de la posición de Ucrania en el ámbito deportivo mundial. La dirección clave del desarrollo de los deportes domésticos es que el autor ve una mayor comercialización y profesionalización de los deportes domésticos.Los autores del artículo afirman que la legislatura ucraniana debería centrar su atención lo antes posible en la provisión normativa de deportes, en particular, para adoptar una serie de enmiendas a la ley actual "sobre cultura física y deportes" o adoptar una nueva ley de deportes y / o la ley "de deportes profesionales".